Consumer Perception Towards Price, Product And Service Of Fast Food Restaurant (Case Study on Kentucky Fried Chicken (KFC) in Rumah Tiga,Teluk Ambon District, Ambon City, Maluku) - Picanussa, Adventio Picanussa; M. Turukay; Maisie T. F. Tuhumury (Cita konsultindo, 2025)
Abstract The aim of this research is to find out the characteristics and perceptions of consumers regarding the prices, products and services of the Kentucky Fried Chicken (KFC) Fast Food Restaurant in Rumah Tiga, Teluk Ambon District, Ambon City, Maluku. The research method used in this research is descriptive statistical analysis and in measuring attitudes, opinions and perceptions of individuals and groups of individuals in this study a Likert scale is used. The method for determining the sample in this study was carried out by chance (accidental sampling) where respondents were taken when they visited the Kentucky Fried Chicken (KFC) Fast Food Restaurant. The research results show the characteristics and also consumer perceptions of prices, products and services of the Kentucky Fried Chicken (KFC) Fast Food Restaurant in Rumah Tiga, Teluk Ambon District, Ambon City, Maluku. Keywords: Consumer Perception, Price, Products and Services